Volume changes in white matter pathways from infancy to early adulthood measured using diffusion tensor based morphometry - Nayak, Amritha; Hafiz, Rakibul; Irfanoglu, M. Okan; Pierpaoli, Carlo (Frontiers in Neurology, 2025)
BackgroundDiffusion tensor imaging (DTI) has proven valuable in assessing structural and architectural features of white matter (WM) in postnatal development. Diffusion tensor-based morphometry (DTBM) uses DTI data to measure local volume changes and has been demonstrated in previous studies to be informative in the evaluation of specific WM pathways in several neurological disorders. In this study, we assess DTBM volume changes during postnatal brain development in typically developing children. In addition, we evaluate in each pathway the relationship between changes in volume and DTI metrics.MethodWe included DTI data from 182 healthy participants in the age range of 0–21 years, from the publicly available database: the NIH Pediatric MRI Data (NIHPD). Data were processed using the TORTOISE pipeline and age-specific templates were created using the diffusion tensor-based registration tool DRTAMAS. Region of interests (ROIs) were defined on a study-specific, young-adult reference template (18–21 years). Individual brains were registered to the reference template using a two-step process involving age-specific templates. ROI values for volume and DTI metrics were normalized to the median values of the 18-21-year group. Developmental trajectories were analyzed in two age segments; Segment 1: data between 0 and 2.69 years and Segment 2: for the remaining age range.ResultsThe results show that volumetric developmental trajectories varied largely among WM regions. The estimated volume at birth ranged: 12–53% of the adult value; where the rate of growth ranged: 3–30% of the adult value per year, in Segment 1; and 0–4% afterwards (Segment 2). The Corticospinal Tract, for example, showed protracted growth into young adulthood, while the Corpus Callosum growth was almost completed in the first 3 years. The magnitude of changes in local volume were generally larger than the magnitude of changes in diffusion metrics. Moreover, volumetric changes were more protracted, i.e., for many regions volume continued to increase even when diffusion metrics had reached a plateau.ConclusionIn conclusion, DTBM has shown developmental trajectories for WM volume in the human brain that are pathway specific and distinct from those obtained for DTI metrics. In future studies, DTBM should be performed in larger cohorts to assess correlation with cognitive and behavioral changes as well as establish ranges for normative values.